Sexual abuse and exploitation of the girl child through cultural practices in Zimbabwe: a human rights perspective - Twinomugisha, B. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2006.